From tradition to the contemporary: changes in the cultural heritage of Barbalha-CE - Silva, Thaís Pereira da (2021)
It addresses the insertions made in the last twenty years at the Santo Antônio festival, in the city of Barbalha, in the interior of the state of Ceará. This celebration has undergone changes, and the main one is its formation, from a religious to a sacred basis, due to the social elements inserted. It is currently registered by the National Historical and Artistic Heritage Institute (IPHAN) as a Brazilian cultural heritage and by the Ceará Secretariat of Culture as a state cultural heritage. The study is exploratory and bibliographical review. To contextualize the theme, we used a theoretical approach derived from Museology and Anthropology, briefly addressing notions of intangible heritage and popular festivals, as well as tradition and modernization in popular manifestations. It is concluded that most of the elements inserted are ways to promote the tourist, economic and social aspect of the celebration, except for the march of groups of feminist activists in the region.